Alexithymia in adolescents with and without pets during the Covid-19 pandemic - Nazila Sahandpour; Mehrangiz Peyvastegar; Roshanak Khodabakhsh pirkalani (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām)
Introduction:  With the spread of the Covid-19 pandemic, many countries in the world implemented necessary quarantines to prevent the spread of the virus. Research shows that quarantine measures can affect mental health; therefore, it is important to identify the psychological characteristics that make people more vulnerable. One of the factors that may increase the occurrence of psychological disorders in adolescents under these conditions is alexithymia. This study was conducted with the aim of investigating alexithymia and its components in adolescents with and without pets during the Covid-19 pandemic. Materials & Methods: The current study employs a descriptive and post-event comparative method, and the statistical population encompasses both adolescents with and without pets. The available sampling method selected 120 people, 60 of whom had pets and 60 of whom did not. The tools of this research were a demographic questionnaire and the Toronto Alexithymia Scale (TAS-20), and data analysis was done using descriptive statistics, independent t-tests, and multivariate analysis of variance (MANOVA) by SPSS version 26 at the level of significance less than 0.05. Results: The results indicated a significant difference in alexithymia between adolescents with and without a pet (t=2.441, P=0.016), with adolescents with a pet exhibiting a higher average of alexithymia compared to those without a pet. In addition, there is a difference between the component of objective thinking in adolescents with and without a pet (F=7.608, P=0.007). This means that the component of objective thinking in female adolescents who have a pet is higher than in male adolescents (F=7.622, P=0.008). Conclusion: The psychological construct of alexithymia significantly differs between adolescents with and without pets during the COVID-19 pandemic. In this case, adolescent girls struggle with objective thinking, tend to focus on concrete events under stress, tend to care for pets more frequently, and struggle with communication skills.